Library 4.0: Eco-Blended Library and Library Inclusion - Rozikin Mochammad; Rindi Ardika MS; Teguh Yudi Cahyono (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2020)
The role of libraries in education today is directed at implementing digitization, called library 4.0. There is a need for service innovation that is able to reach the needs of the digital natives. This study describes and analyzes the innovation of Library Services 4.0: Eco-Blended Libraries and Inclusion-Based Library at Universitas Negeri Malang’s Library. This research uses descriptive qualitative method. The data were obtained through interviews with librarians, observation and documentation. The results showed that in an effort to create a library ecosystem 4.0, the library has succeeded in implementing innovations. These innovations are in the form of an Eco-Blended Library program such as an e-book garden, Beringin Baca, a children's play ground, a library café, art performances, movie talk, and discussion booths. In addition, inclusion-based library is also developed with the Integrated Library Information System (SIPADU) facility digitizing collections in collaboration with Indonesia OneSearch, chat reference services, online loan and extension library collections, as well as information literacy. As a suggestion, the library needs to increase the number of human resources who might more focus on digital library services, further encouraging human resources to conduct online scientific publications and participate in online training forums or groups.